2015
DOI: 10.5897/ajmr2014.6809
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infections in post-operative wounds due to Staphylococcus aureus and Pseudomonas aeruginosa in Benue State Nigeria

Abstract: Three hundred (300) post-operative wound swab specimens were aseptically collected from four hospitals and investigated. The four hospitals were Federal Medical Centre, Makurdi (FMCM), General Hospital, Gboko (GHG), General Hospital, Otukpo (GHO) and General Hospital North Bank, Makurdi (GHNBM). The swabs were cultured and organisms identified according to standard procedures. A prevalence rate of bacterial isolates (56.7%) was obtained from the post-operative wound sites investigated. Pseudomonas aeruginosa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(22 reference statements)
0
3
1
Order By: Relevance
“…The isolation rate was higher in surgical wound samples; 24/200 (12%) than blood samples (2%). Our findings were higher than other reports, where E faecalis was isolated from wound swabs with percentages of 6% 30 and 1.3%, 31 and were lower than others where the isolation rate from blood cultures was (4.6%). 32 Our study showed that all isolates were reported to be resistant to cefepime, ampicillin, tetracycline, and exhibited high resistance rates; (84.6%) to rifampin, and (69.2%) to amoxicillin-clavulanic, that are comparable to other reports.…”
Section: Discussioncontrasting
confidence: 93%
“…The isolation rate was higher in surgical wound samples; 24/200 (12%) than blood samples (2%). Our findings were higher than other reports, where E faecalis was isolated from wound swabs with percentages of 6% 30 and 1.3%, 31 and were lower than others where the isolation rate from blood cultures was (4.6%). 32 Our study showed that all isolates were reported to be resistant to cefepime, ampicillin, tetracycline, and exhibited high resistance rates; (84.6%) to rifampin, and (69.2%) to amoxicillin-clavulanic, that are comparable to other reports.…”
Section: Discussioncontrasting
confidence: 93%
“…High rate resistance to various antimicrobial agents particularly among nosocomial organisms were revealed and become serious challenge in diseases treating (29,30), Report of WHO agrees with the truth of wide use of antimicrobial agents in outside and inside of medicine has a critical role in dissemination of bacterial resistant strains by involving various resistance mechanisms like production of Beta-lactamase enzymes that destruct these drugs [31]. The great difficulty of the bacterial resistance is the misuse and overuse of antimicrobial agents by patients in addition to the doctors (32,33), and it could be because of the erratically uses of antimicrobial agents without laboratory diagnosis and antimicrobial sensitivity test.…”
Section: Resultsmentioning
confidence: 99%
“…P. aeruginosa is considered as a common isolated bacterium from clinical specimens that causes a significant challenge for treating both nosocomial and community-acquired infections. P. aeruginosa has also been implicated as a prominent cause of post-operative wound infection in Nigeria [19]. It is one of the most important opportunistic pathogens responsible for 10-15% of nosocomial infections worldwide [1].…”
Section: Discussionmentioning
confidence: 99%